Multiliteracy Transformation in Madrasah: Cultural and Civic Development Design - Panai, Abdul Haris; Cuga, Candra; Sarlin, Muhammad; Halid, Siti Nurhasanah (Universitas Negeri Gorontalo, 2024)
This study aims to develop a cultural and civic literacy programme design in Madrasah Ibtidaiyah using Thiagarajan's 4D tool development model, which includes four stages: defining, designing, developing and disseminating. The problem formulations studied include (1) how to design the development of cultural literacy and citizenship of Madrasahs in MIM Unggulan Kota Gorontalo and (2) the feasibility of the developed programme design. Data were obtained through interviews, documentation and validation by experts. The results showed that the design of the cultural and civic literacy programme consists of three main aspects, namely habits (habituation), institutions, and integration in learning. The programme was validated by experts and declared feasible to be implemented at MIM Unggulan Gorontalo City. The implementation of this programme is expected to increase the sense of nationalism, form reasonable and responsible student characters, encourage creativity, and strengthen national unity. This research contributes to the development of cultural and civic literacy education, especially at the basic education level.